Can We Improve Treatment Decision-Making for Incapacitated Patients? - Rid, Annette (The Hastings Center report, 2010)
When patients cannot make their own treatment decisions, surrogates typically step in to do it for them. Surrogate decision-making is far from ideal, of course, as the surrogate may not know what the patient prefers or what best promotes her interests. One way to improve it would be to arm surrogates with information about what patients in similar circumstances tend to prefer, allowing them to make empirically grounded predictions about what their patient would want.